Divide 86/63 and 43/53

86
63
÷
43
53
=
1
43
63

What is 86/63 ÷ 43/53

86
63
÷
43
53
=

keep the first fraction the same, and flip the second fraction so that the numerator becomes denominator and the denominator becomes numerator, then multiply numerators together and denominator together

86
63
÷
43
53
=
86 x 53
63 x 43
=
4558
2709

Simplify the fraction

Divide each part of the fraction with the greatest common factor to simplify the fraction

4558
2709
=
4558 ÷ 43
2709 ÷ 43
=
106
63

Because the numerator greater than the denominator, so we have an improper fraction, which means we can simplify it by converting the improper fraction to a mixed number.

Improper fraction to mixed number, get the whole number by dividing the numerator with the denominator, then subtract the numerator by the whole number multiplied by the denominator.

106
63
=
106 ÷ 63 = 1 +
106 - (1 x 63)
63
=
1
43
63

Fraction Calculator

📌 Negative signs in fractions

Positive Fractions

-1
-2
=
-
1
-2
=
-
-1
2
=
1
2

Negative Fractions

-1
2
=
1
-2
=
-
-1
-2
=
-
1
2